Pendampingan Pemanfaatan Aplikasi Pembelajaran Berbasis Teknologi Pada Mata Pelajaran Akidah Akhlak di Mts Negeri 2 Kayong Utara - Azizah, Siti Nur; Husni, Muhammad (Belalek, 2025)
This mentoring activity aims to increase students' learning motivation through the use of the Quizizz digital platform, specifically in the subject of Akidah Akhlak. In this era of rapid technological development, the integration of interactive learning media is crucial in attracting students' interest and increasing learning effectiveness. The method used in this PKM is intensive training and direct assistance to Akidah Akhlak teachers at MTs Negeri 2 Kayong Utara, focusing on the use of Quizizz features in designing quizzes and engaging learning activities. This activity was carried out on November 17-21, 2025. The results of this activity showed a significant increase in student engagement during the learning process, which was reflected in their enthusiasm and active participation in answering questions and discussions. Teachers also reported that Quizizz helped them create a more dynamic and interactive learning environment, as well as simplify the process of evaluating students' understanding of Akidah Akhlak material. Thus, this PKM proves that the appropriate use of technology can provide great benefits for students and teachers in improving the quality of Akidah Akhlak learning in this digital era.